IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY BY PT PERTAMINA (PERSERO) BRANCH OF BIMA - Fitrah, Muhammad (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
Indonesia is one of the countries in the world that obliged every corporation to reserve funds as Corporate Social Responsibility (CSR). It is explicitly regulated in Law Number 40 of 2007 concerning Limited Company, social and environment responsibility also obliged to the state companies (BUMN) which activities are in the field of natural resource exploitation. Pertamina as a National energy company with world class reputation holds commitment and concern toward CSR to contribute solving global issue related to sustainable development. Implementation of CSR by PT. Pertamina (Persero) branch Bima has not completely contributes positive value to community economic development, as the programs so far not provide sense of fairness yet to the community.Keywords: Corporate Social Responsibility, Pertamina